Pengaruh Kesesuaian Penempatan Kerja terhadap Prestasi Kerja Pegawai (Studi pada Pegawai Kantor BAPPEDA Kabupaten Nabire, Papua) - Pesiwarissa, Eduard L (Jurnal Aplikasi Manajemen, 2008)
This research explains the influence of Positioning Appropriateness Toward the Employee Performance (A Study on the Employees of me Agency for Regional Development (BAPPEDA) at the Nabire Regency, Papua. Objective of this research is to analyze good influences, both simultaneously and partially, among positioning based on knowledge, skill, and attitude appropriateness toward the employee of BAPPEDA ar me Nabire Regency; Papua. The analysis technique uses multi-regression analysis and result of this analysis shows that the appropriateness variables for knowledge (X1), skill (X2), and attitude (X3) have simultaneously significant influence toward working performance of the employee (Y). While knowledge appropriateness variable has dominant influence toward working performance of the employee.